(untitled) (Experimental biology, 2023)
This article presents the results of many years of research on the wetland and coastal aquatic flora of the Ketpen Ridge. The paper presents an analysis of the wetland and coastal-aquatic floristic complex of the Ketpen Ridge. The taxonomic diversity of the species composition of the wetland and coastal-aquatic floristic complex, the biomorphological analysis of the life forms of wetland and coastal-aquatic species, as well as the belonging of wetland and coastal-aquatic species to different geographical types of habitats were revealed. A detailed floristic analysis of wetland and coastal aquatic flora made it possible to identify 211 species of vascular plants belonging to 101 genera and 39 families. in its composition 151 species. Analysis of the species richness of the genera of the wetland and coastal aquatic flora of the Ketpen Ridge shows that out of 83 genera, 6 genera are large.